Examining Differences in Bias Homicide Across Victim Groups. (March 2018) - Gruenewald, Jeff; Allison, Kayla
Little is known about how situations of bias homicide might vary dependent upon who is targeted. Drawing from doing difference theory, we comparatively examine several event-level variables for bias homicide involving three different target groups. Data on bias homicide occurring in the United States come from the U.S. Extremist Crime Database (ECDB). Our findings reveal significant differences across bias victim groups, specifically regarding weapon use, location of incidents, victim–offender relationships, and victim and offender demographics. The results of this study have important implications for the theoretical and methodological advancement of empirical research on bias crime and for law enforcement responsible for identifying and investigating bias crimes.